Method for preparing surface-modified microfibrillated cellulose

By covalently combining surfactant and silane compounds with phenolic compounds in water, a hydrophobic dried microfibrillated cellulose powder was prepared, which solved the dispersion and compatibility of nanocellulose in hydrophobic materials. Efficient and economical production and improved mechanical properties are achieved.

CN119256020APending Publication Date: 2025-01-03DATWYLER SCHWEIZ AG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042771.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art faces difficulties in removing water and low compatibility problems between hydrophilic cellulose substrates and hydrophobic substrates when incorporated into hydrophobic materials, resulting in uneconomical drying processes of high energy and time-intensive drying. Moreover, commonly used surface modification methods increase the cost of fillers and reduce the mechanical properties.

Method used

By providing a microfibrillated cellulose suspension in water, adding a surfactant and a silane compound to form a covalent bond with a phenolic compound, covalent bonding and plasticizer are performed, and hydrophobic is prepared by conventional drying methods The dry powder avoids the use of organic solvents and the production of toxic waste.

Benefits of technology

Good dispersion and high scalability in hydrophobic matrix are achieved, production costs are reduced, mechanical properties of cellulose materials are improved, and the use of organic solvents and waste generation are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256020A_ABST
    Figure CN119256020A_ABST
Patent Text Reader

Abstract

A method for preparing hydrophobic, dry, surface-modified fibrillated cellulose to improve its dispersibility in a hydrophobic matrix comprises the steps of: a.) providing a suspension of microfibrillated cellulose from 5 to 30 wt%, preferably from about 7 to 11 wt%, in water; b.) adding a surfactant to the suspension in a mass ratio of surfactant to microfibrillated cellulose suspension of 0.1 to 2.0 wt%, preferably 0.5 to 1.0 wt%, more preferably about 0.8 wt%; c.) adding a surface modifier to the suspension in a mass ratio of surface modifier to microfibrillated cellulose dry matter of 20 to 300 wt%, preferably 80 to 120 wt%, more preferably about 100 wt%, where the surface modifier is obtained by a chemical reaction of a silane compound with a phenolic compound to form a covalent bond between the silane compound and the phenolic compound; d.) covalently binding the surface modifier with the microfibrillated cellulose by (i) hydrolysis of the surface modifier to form a reactive silanol group (R-Si-OH) and (ii) condensation of the silanol group of the surface modifier with the available OH-group of the microfibrillated cellulose; e.) adding a plasticizer to the surface-modified microfibrillated cellulose suspension; f.) drying the suspension to remove water and obtain a dry powder of surface-modified microfibrillated cellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing hydrophobic dry surface-modified fibrillated cellulose to improve its dispersibility in a hydrophobic matrix. Background Art

[0002] As is known, wood is made of a cellulose matrix. The fibers that form this matrix are bundles of fibrils, which in turn consist of small elements called microfibrils. From a chemical point of view, cellulose is a polymer formed by the polymerization of cellobiose monomers. Cellobiose monomers are also composed of two glucose molecules (disaccharides) bonded in β-1,4-glycosidic bonds. Through the fibrillation process, cellulose fibers are separated from their source materials (such as wood, grass and agricultural waste) into a three-dimensional network of microfibrils with a large surface area. These tangled fibrils are called "micro-fibrillated cellulose" (MFC). Microfibrillated cellulose (MFC) can be further processed into thinner nanofibrillated cellulose (NFC).

[0003] Due to availability, natural resources and excellent mechanical properties, substrates based on cellulose, such as cellulose fibers or fibrillated cellulose, are gaining more and more interest as filling materials for different composite materials.

[0004] However, there are two major challenges in incorporating nanocellulose into hydrophobic materials: (1) the removal of water from native cellulosic materials, which has proven difficult due to the strongly hydrophilic nature of cellulose and the tendency of such materials to irreversibly aggregate and / or keratinize during water removal and / or drying; and (2) the low compatibility between the hydrophilic cellulose substrate and the hydrophobic matrix.

[0005] In order to prevent or reduce irreversible aggregation, time-intensive and energy-intensive drying processes are usually used, such as freeze drying, supercritical drying and / or solvent exchange drying. Due to high energy / time and / or organic solvent consumption, these processes are usually only used on a laboratory scale, which is uneconomical for the commercial production of nano cellulose. In order to improve compatibility, various surface modifications can be carried out to cellulose substrates to increase the hydrophobicity of cellulose materials. The surface of nano cellulose can be modified by esterification, acetylation acylation, molecule and / or polymer grafting, carbamateization (urethanization). (References: (1)Habibi Youssef(2014).Key advances in the chemicalmodification of nanocellulose.Chem.Soc.Rev.2014,43,1519DOI:10.1039 / C3CS60204D.(2)Eyley Samuel and Thielemans Wim(2014).Surface modification ofcellulose nanocrystals. Nanoscale, 2014, 6, 7764-7779.).

[0006] Most of these reactions are sensitive to moisture and water, so the reactions need to be carried out in organic solvents without the presence of water. This requires the removal of water from the cellulose substrate prior to surface modification, which faces the same challenges as (1) above.

[0007] To avoid removing water and pre-drying the cellulose fibers before surface modification, the following methods are usually used: (i) non-covalent surface modification (such as coating) or (ii) water-resistant chemical reaction (such as silylation); or (iii) a combination of (i) and (ii).

[0008] WO2020086419 describes a method for preparing a nanocellulose masterbatch with improved nanocellulose dispersibility in an elastomeric compound. The method uses a separator containing carbon black, an elastomer latex and a wax as a compatibilizer that forms a non-covalent bond with the nanocellulose. These compositions can avoid cellulose aggregation when dried in the masterbatch preparation.

[0009] WO2021070899 describes a method for preparing nanocellulose masterbatch using a surfactant, resorcinol-formaldehyde oligomers, formaldehyde, and rubber latex. The surfactant and the resorcinol-formaldehyde resin as a compatibilizer improve the dispersibility of nanocellulose in rubber latex.

[0010] The disadvantages of using the nanocellulose masterbatch prepared by the above method for final applications are (1) low compatibility with different rubber formulations for various final applications; (2) possible increase in filler costs (e.g., additional processing, transportation, and storage); and (3) little improvement in the mechanical properties of rubber compounds that do not have cross-linkable functional groups on the cellulose surface.

[0011] Instead, these drawbacks are addressed by avoiding the use of latex and / or by grafting the modifier onto the cellulose surface. The modifier needs to have at least two types of functional groups, one that reacts with the hydroxyl groups of cellulose to form a covalent bond and another that can form a covalent linkage with the elastomeric matrix during the rubber curing process.

[0012] WO2020142793 describes improved compositions and methods for dispersing and drying nanocellulose for polymer composites. The disclosed nanocellulose dispersion concentrates contain nanocellulose and nanocellulose-containing composite products, wherein the dispersant / drying agent is selected from the group consisting of waxes, polyolefins, olefin maleic anhydride copolymers, olefin acrylic acid copolymers, polyols, fatty acids, fatty alcohols, polyol glycerides, polydimethylsiloxanes, polydimethylsiloxane alkyl esters, polyacrylamides, starches, cellulose derivatives, particles, and combinations or reaction products thereof.

[0013] WO2017219145 describes a method for preparing a hydrophobic cellulosic material using a modified styrene-maleic anhydride copolymer in an aqueous solution. The anhydride groups may react with cellulose and water in the solvent. After reacting with cellulose, covalent ester bonds may be formed. After reacting with water, the copolymer may be used as a coating polymer on the surface of cellulose. During the rubber curing process, the functional groups of the styrene may further form a connection with the rubber polymer. Summary of the invention

[0014] The object of the present invention is to provide an alternative process for the preparation of hydrophobic dry surface-modified fibrillated cellulose to improve its dispersibility in hydrophobic matrices. Another object is to provide a process applicable to highly concentrated fibrillated cellulose pastes. Another object is to provide a process which avoids the consumption of organic solvents and the generation of (toxic) wastes in the whole process.

[0015] At least one of the objects of the present invention is achieved by a method according to claim 1. A method for preparing hydrophobic dry surface-modified fibrillated cellulose to improve its dispersibility in a hydrophobic matrix comprises the following steps: a.) providing a suspension of microfibrillated cellulose in water at 5 to 30 wt%, preferably about 7 to 11 wt%; b.) adding a surfactant to the suspension in a mass ratio of 0.1 to 2.0 wt%, preferably 0.5 to 1.0 wt%, more preferably about 0.8 wt% of the surfactant to the microfibrillated cellulose suspension; c.) adding a surface modifier to the suspension in a mass ratio of 20 to 300 wt%, preferably 80 to 120 wt%, more preferably about 100 wt% of the surface modifier to the microfibrillated cellulose dry matter; d.) adding a surface modifier to the suspension, wherein the surface modifier is obtained by chemical reaction of a silane compound with a phenolic compound to form a covalent bond between the silane compound and the phenolic compound; d.) covalently bonding the surface modifier to the microfibrillated cellulose by: (i) hydrolysis of the surface modifier to form reactive silanol groups (R-Si-OH) and (ii) condensation of the silanol groups of the surface modifier with the available OH-groups of the microfibrillated cellulose; e.) adding a plasticizer to the surface-modified microfibrillated cellulose suspension; f.) drying the suspension to remove water and obtain a dry powder of the surface-modified microfibrillated cellulose.

[0016] The product of the process is a dry powder of hydrophobic, surface-modified fibrillated cellulose, which is suitable as a filling material for various composite materials, wherein the matrix material of the composite material is also hydrophobic.

[0017] In the context of the present invention, the term "dry powder" is understood as a final compound of surface-modified microfibrillated cellulose having a water content of less than 10 wt%, preferably 5 wt% (residual humidity present in the product). Since the final compound comprises surfactants, surface modifiers and plasticizers, the final compound may be more of a powdery material.

[0018] The method avoids the consumption of organic solvents and thus also avoids the generation of (toxic) waste due to solvents. Furthermore, the method can be applied directly to paste-like concentrated fibrillated cellulose in water without the use of solvents.

[0019] It also has high scalability to prepare large amounts of surface-modified microfibrillated cellulose.

[0020] It also allows the use of conventional drying methods and facilities to prepare dry powders of surface modified microfibrillated cellulose. Conventional drying techniques may include, but are not limited to, evaporation, spray drying, spin flash drying, high shear mixing and drying, drum drying.

[0021] Further embodiments of the invention are set forth in the dependent claims.

[0022] In some embodiments, the hydrolysis and partial condensation may be conducted at 20 to 120°C, preferably at about 120°C, over a period of at least 5 minutes to up to 4 hours, preferably about 2 hours.

[0023] In some embodiments, drying and further condensation may be performed at 20 to 130° C., preferably at about 60° C. Good results have been achieved at about 60° C. for about 24 hours.

[0024] In some embodiments, drying and further condensation may be performed at a pressure of 5 mbar to 1000 mbar.

[0025] In some embodiments, drying and further condensation may be performed until a dry powder having a moisture content of less than 10 wt %, preferably less than 5 wt %, is obtained.

[0026] In some embodiments, the fibrillated cellulose may be nanofibrillated cellulose having a particle length in the range of 1 to 500 nm, or microfibrillated cellulose having a particle length in the range of 100 nm to 500 μm, and / or the diameter of the fibrils of the microfibrillated cellulose may be in the range of 1 nm to 100 nm.

[0027] In some embodiments, the silane compound may contain at least a primary or secondary amine functional group and may be selected from the group consisting of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyldimethylethoxysilane, 1-amino-2-(dimethylethoxysilyl)propane, 3-aminopropyldiisopropylethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyl ...

[0013] The present invention relates to butylaminopropyltrimethoxysilane, tert-butylaminopropyltrimethoxysilane, (N-cyclohexylaminomethyl)methyldiethoxysilane, (N-cyclohexylaminomethyl)triethoxysilane, (N-cyclohexylaminopropyl)trimethoxysilane, (3-(N-ethylamino)isobutyl)methyldiethoxysilane, N-methylaminopropylmethyldimethoxysilane, N-methylaminopropyltrimethoxysilane, (phenylaminomethyl)methyldimethoxysilane, N-phenylaminomethyltriethoxysilane, N-phenylaminopropyltrimethoxysilane and combinations thereof. At least 3-aminopropyltriethoxysilane (APTES) has been used to achieve good results.

[0028] In some embodiments, the phenolic compounds may have the following common structure:

[0029]

[0030] wherein at least one of the substituents R1 and R1 at the ortho position of the -OH group is hydrogen H; wherein at least one other substituent at the meta position R3 and R4 or the para position R5 of the -OH group comprises a hydrocarbon backbone in the range of C2 to C30, preferably comprising at least one unsaturated π bond. The hydrocarbon backbone may comprise halogens, or nitrogen, or sulfur and / or functional groups selected from thiols, epoxides, disulfides, polysulfides, amines, ketones, hydroxyls, carboxylic acids, amines and ketones.

[0031] In some embodiments, the phenolic compound may be selected from the group consisting of cardanol, eugenol, anacardol, campnospermanol, promalabaricones, elenic acid, plakinidone, anacardic acid, anagigantic acid, pelandiauic acid, ginkgolic acid, frutesins, microphyllinic acid, merulinic acid, urushiol, bhilavanol, renghol, thitsiol, laccol, urushiol, glutarenghol, gingerol, shogaol, zingerone, and combinations thereof. Good results have been achieved with at least cardanol.

[0032] In some embodiments, the surfactant may be selected from the group consisting of docusate sodium or silicone-containing surfactants, polyoxyethylenesorbitanmonolaurate, polyoxyethylenesorbitanmonolaurate, octylphenol ethoxylate, polyethylene sorbitan esters, sodium lauryl sulfate, and combinations thereof.

[0033] In some embodiments, the plasticizer is selected from the group consisting of mineral oil, butylcarbitoladipate, ether thioether aromatic extracts, and combinations thereof. Good results have been achieved with at least mineral oil.

[0034] In some embodiments, a molar ratio between the silane compound and the phenolic compound may be in a range of 0.5:1 to 2:1.

[0035] In some embodiments, the plasticizer may be added at a mass ratio of 10 to 200 wt %, preferably 50 to 150 wt % of the plasticizer to the microfibrillated cellulose dry matter.

[0036] In some embodiments, no other solvent is used except water, ie, the method can be performed without using, for example, organic solvents.

[0037] The present invention also relates to the use of the dried surface-modified fibrillated cellulose prepared according to the above method as a reinforcing filler for polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present invention will be described in more detail below with reference to the embodiments shown in the accompanying drawings. The accompanying drawings show:

[0039] Figure 1 Example stress (N / mm 2 ) and elongation (%). DETAILED DESCRIPTION

[0040] Example of MFC filler modified by APTES-cardanol

[0041] The laboratory-scale synthesis involves surface modification of MFC aqueous suspensions from two different sources. The modification consists in chemically reacting a mixture of APTES (3-aminopropyltriethoxysilane) and cardanol (phenolic lipid) using surfactants and mineral oil as reaction media to make the surface properties of MFC hydrophobic. The mixture is then dried to obtain the final product.

[0042]

[0043] The synthesis conditions of the surface modifier APTES-cardanol were as follows: 167 g cardanol (560 mmol), 123.8 g APTES (560 mmol), 33.6 g paraformaldehyde (1.12 mmol), and the mixture was reacted at 65° C. for 6 hours.

[0044] Reaction conditions: (1) mixing MFC with surfactant at 1000 rpm at room temperature for 30 minutes; (2) adding and mixing APTES-cardanol; (3) hydrolysis and partial condensation at about 120°C during about 2 hours; (4) adding mineral oil as a plasticizer, and (5) drying in an oven at 60°C for 48 hours, where further condensation occurs.

[0045] Proof of concept:

[0046] The dried modified MFC reacted as above was compounded in an EPDM (ethylene propylene diene monomer) matrix. Subsequently, the compound was vulcanized. The properties have been compared with the vulcanized compound without synthetic aramid fibre and with synthetic aramid fibre instead of the modified MFC reinforced.

[0047]

[0048] Figure 1 The stress (N / mm) of different compounds is shown. 2 ) versus elongation (%). The modified MFC exhibits good stability, dispersibility and processability in a hydrophobic elastomer matrix (here EPDM). Its physical and mechanical properties are improved compared to the control compounds (without MFC or aramid fibers, and reinforced with synthetic aramid fibers).

Claims

1. A method for preparing hydrophobic dry surface-modified fibrillated cellulose to improve its dispersibility in a hydrophobic matrix, the method comprising the following steps: a. Providing a suspension of 5 to 30 wt%, preferably about 7 to 11 wt% microfibrillated cellulose in water; b. adding a surfactant to the suspension in a mass ratio of 0.1 to 2.0 wt %, preferably 0.5 to 1.0 wt %, more preferably about 0.8 wt % of the surfactant to the microfibrillated cellulose suspension; c. adding a surface modifier to the suspension at a mass ratio of 20 to 300 wt %, preferably 80 to 120 wt %, more preferably about 100 wt % of the surface modifier to the microfibrillated cellulose dry matter, wherein the surface modifier is obtained by a chemical reaction of a silane compound with a phenolic compound to form a covalent bond between the silane compound and the phenolic compound; d. covalently bonding the surface modifier to the microfibrillated cellulose by: (i) hydrolysis of the surface modifier to form reactive silanol groups (R—Si—OH) and (ii) condensation of the silanol groups of the surface modifier with the available OH-groups of the microfibrillated cellulose, e. adding a plasticizer to the surface-modified microfibrillated cellulose suspension; f. Drying the suspension to remove water and obtain a dry powder of surface-modified microfibrillated cellulose.

2. The process according to claim 1, wherein the hydrolysis and partial condensation are carried out at 20 to 120°C, preferably at about 120°C, over a period of at least 5 minutes up to 4 hours, preferably about 2 hours.

3. The process according to any one of the preceding claims, wherein the drying and further condensation are carried out at 20 to 130°C, preferably at about 60°C and / or at a pressure of 5 mbar to 1000 mbar.

4. A process according to any one of the preceding claims, wherein drying and further condensation are carried out until a dry powder is obtained having a moisture content below 10 wt%, preferably below 5 wt%.

5. The method according to any one of the preceding claims, wherein the particle length of the microfibrillated cellulose is in the range of 100 nm to 500 μm and / or the diameter of the fibrils of the microfibrillated cellulose is in the range of 1 nm to 100 nm.

6. The method according to any one of the preceding claims, wherein the silane compound comprises at least a primary or secondary amine functional group and is selected from the group consisting of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyldimethylethoxysilane, 1-amino-2-(dimethylethoxysilyl)propane, 3-aminopropyldiisopropylethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyl-trimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, silane, N-butylaminopropyltrimethoxysilane, tert-butylaminopropyltrimethoxysilane, (N-cyclohexylaminomethyl)methyldiethoxysilane, (N-cyclohexylaminomethyl)triethoxysilane, (N-cyclohexylaminopropyl)trimethoxysilane, (3-(N-ethylamino)isobutyl)methyldiethoxysilane, N-methylaminopropylmethyldimethoxysilane, N-methylaminopropyltrimethoxysilane, (phenylaminomethyl)methyldimethoxysilane, N-phenylaminomethyltriethoxysilane, N-phenylaminopropyltrimethoxysilane and combinations thereof.

7. The method according to any one of the preceding claims, wherein the phenolic compounds have the following common structure: wherein at least one of the substituents R1 and R2 at the ortho position of the -OH group is hydrogen H; Wherein at least one other substituent at the meta position R3 and R4 or the para position R5 of the -OH group comprises a hydrocarbon backbone in the range of C2 to C30, preferably comprising at least one unsaturated π bond.

8. The method of claim 7, wherein the hydrocarbon backbone comprises halogens, or nitrogen, or sulfur and / or functional groups selected from thiols, epoxides, disulfides, polysulfides, amines, ketones, hydroxyls, carboxylic acids, amines and ketones.

9. The method according to any one of the preceding claims, wherein the phenolic compound is selected from the group consisting of cardanol, eugenol, anacardol, cannourushiol, promalabadone, elenic acid, plakinidone, anacardic acid, anagigantic acid, pelandiauic acid, ginkgolic acid, frutesins, microphyllinic acid, mycelial acid, urushiol, bhilavanol, renghol, urushiol, urushiol, urushiol, glutarenghol, gingerol, shogaol, zingerone, and combinations thereof.

10. The method according to any one of the preceding claims, wherein the molar ratio between the silane compound and the phenolic compound is in the range of 0.5:1 to 2:

1.

11. The method according to any one of the preceding claims, wherein the surfactant is selected from the group consisting of docusate sodium or silicone-containing surfactants, polyoxyethylene sorbitan monolaurate; polyethylene glycol sorbitan monolaurate, octylphenol ethoxylate, polyethylene sorbitan esters, sodium lauryl sulfate, and combinations thereof.

12. The method according to any one of the preceding claims, wherein the plasticizer is selected from the group consisting of mineral oil, butyl carbitol adipate, ether thioether aromatic extracts, and combinations thereof.

13. The method according to any one of the preceding claims, wherein the plasticizer is added in a mass ratio of 10 to 200 wt%, preferably 50 to 150 wt% of plasticizer to microfibrillated cellulose dry matter.

14. The process according to any one of the preceding claims, wherein besides water no other solvents are used.

15. Use of the dried surface modified fibrillated cellulose according to any one of the preceding claims as a reinforcing filler for polymeric materials.